Interest Rates, Inflation, and Banking Stock Returns: An Error Correction Model Approach - Herman Paleni; Suyadi; Yulpa Rabeta; Meiza Marlingga Putri (CV. Sakura Digital Nusantara, 2026)
Purpose – This study analyzes the long- and short-run relationships between interest rates, inflation, and stock returns in Indonesia’s banking sector in Indonesia. Design/methodology/approach – The research employs monthly time-series data from 2020 to 2024, covering banking listed on the Indonesia Stock Exchange, the study applies stationarity and cointegration tests followed by the Error Correction Model (ECM) to examine short-run dynamics and long-run equilibrium adjustments. Finding/Results – The results reveal a significant long-run relationship among the variables, indicated by a negative and statistically significant Error Correction Term (ECT). The ECT coefficient, close to –1, suggests rapid adjustment toward equilibrium, while short-run changes in interest rates and inflation do not significantly affect stock returns. Originality/Value – These findings confirm the dynamic interaction among variables and the importance of the error-correction mechanism in restoring long-run equilibrium. This provides empirical evidence on the short- and long-run effects of macroeconomic variables on banking stock returns in Indonesia, offering insights into macroeconomic influences on sectoral stock performance during the post-pandemic period.